Role and Mechanism of Rhizopus Nigrum Polysaccharide EPS1-1 as Pharmaceutical for Therapy of Hepatocellular Carcinoma - Chu, Guangyu; Miao, Yingying; Huang, Kexin; Song, Han; Liu, Liang (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: This work is to study the effect of Rhizopus nigrum polysaccharide EPS1-1 on hepatocellular carcinoma (HCC) in vitro and in vivo. Methods: HepG2 and Huh-7 cells and nude mice models of liver cancers were used in this study. The cells and nude mice were treated with EPS1-1 at different concentrations. The CCK8 assays were used to measure the proliferation activities of cells, apoptosis was determined with flow cytometry, cell migration was measured by wound-healing assays, cell invasion was evaluated by Transwell assay, and the survival periods of different groups of tumor-bearing mice were compared. Real-time PCR and Western blot were used to measure the expression levels of mRNAs and proteins of the genes related to proliferation, apoptosis, migration, and invasion. Results:In vitro experiments revealed that when treated with EPS1-1, HepG2 and Huh-7 cell proliferation activities decreased, while there was an increase for the apoptosis rate, and the migration and invasion capabilities were significantly reduced. In vivo experiments showed that EPS1-1 could significantly reduce the tumor growth and lung metastasis of HCC, and prolong the survival periods of tumor-bearing nude mice. Furthermore, EPS1-1 has no apparent damage to the heart, liver, and kidney. Further studies showed that EPS1-1 could affect the expression of proliferation-related genes CCND1 and c-Myc, apoptosis-related genes BAX and Bcl-2, and migration and invasion related genes Vimentin and Slug, thereby affecting the biological process of HCC. Conclusion: EPS1-1 can inhibit the malignant process of HCC in vitro and in vivo, which indicates that EPS1-1 has the potential value of clinical application as chemotherapy or adjuvant in the treatment of liver cancer.